Information retention and overload in first-time hearing aid users: an interactive multimedia educational solution - Ferguson, Melanie A.; Brandreth, Marian; Brassington, William; Wharrad, Heather (ASHA, 2015)
Purpose: An educational intervention to improve knowledge of hearing aids and communication in first-time hearing aid users was assessed. This intervention was based on the concept of reusable learning objects (RLOs).